Instantaneous and prolonged effects of a triple density midsole during standing and walking tasks - LeVangie, M.; Nigg, S.; Nigg, B. M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to determine if there were any biomechanical differences between an unstable triple density midsole (TRIPLE) and a stable single density midsole (CONTROL). Twelve females completed 10 walking trials and three static trials followed by a two hour prolonged activity assessment during which participants alternated between standing and walking on a treadmill. Muscle activity, center of pressure, plantar forces and tissue oxygenation were measured for each footwear condition on two separate days. Standing in the TRIPLE condition resulted in better pressure distribution and lower peak forces, while walking in the TRIPLE condition resulted in greater tissue oxygenation. This midsole could be incorporated into other footwear where prolonged exposure to standing and walking tasks are the norm, such as work boots.